Anti-obesity and anti-oxidative effects of methanolic Albizia myriophylla (L. Benth) bark extract in obese mice - Sa'at, Azmah (2017)
Globally and in Malaysia, obesity causes early morbidity and mortality and is costly to treat.The antioxidant activities in herbal plants have been suggested as one of the mechanisms working against obesity. Hence, this study examined the antioxidant activity of Albizia myriophylla bark or known locally as tebu gajah. Its effect on anti-obesity via in vivo test in high-fat diet-induced obesity in mice consisting of the normal control group (NC), the high-fat diet control group (HFDC), the high fat diet group treated with Albizia myriophylla methanol extract at 10 mg/kg, 20 mg/kg and 30 mg/kg for 5 weeks. Antioxidant activity of the methanol extract and its derived fractions namely hexane, chloroform, ethyl acetate, butanol and a residual aqueous fraction of the bark of ABZ was assessed. In (1,1-diphenyl-2-picrylhidrazyl) radical scavenging test, (2-2’-azinobis 3-ethyl-6-sulfonic acid) radical scavenging test and reducing activity on ferrous iron test, the total antioxidant capacity was found to be varied in different fractions. The IC50 calculated value of the three assays showed that the methanolic extract of ABZ bark had the lowest IC50 value for each assay, compared to the other extracts signifying highest antioxidant activity and was selected for use in the anti-obesity study. The body weight of mice, adipose cellularity study, and levels of cholesterol, triglyceride, low-density lipoprotein (LDL), the malondialdehyde levels in the muscles of the obese mice, the serum aspartate transaminase (AST) and serum alanine transaminase (ALT) were analysed. Results showed significant weight loss with significant reduction in the number and size of adipose cells in the mice treated with 20 mg/kg and 30 mg/kg of methanolic extract of ABZ bark.Inaddition, there was a significant reduction of blood cholesterol, triglyceride and LDL following treatment with 20 mg/kg and 30 mg/kg of methanolic extract of ABZ bark, compared to HFDC. Furthermore, the significant reduction of AST, ALT and malondialdehyde in the 20 mg/kg and 30 mg/kg treated group, compared with HFDC, suggest the safety of methanolic extract of ABZ bark in a mice model. The regulatory effects of methanolic extract of ABZ bark on genes including hormone sensitive lipase (HSL), peroxisome proliferator-activated receptors α and γ (PPAR α and PPAR γ), sterol regulatory element-binding protein-2 (SREBP2) and Stearoyl-Coenzyme A-Desaturase (SCD) gene expression and adipocytokines including tumor necrosis factor-α (TNFα), interleukin-6 (IL-6), adiponectin and leptin involved in lipid metabolism were also studied. The obese mice treated with the 30 mg/kg of methanolic extract of ABZ showed significant up-regulated of PPARα and significant down-regulated activity of PPARγ, SREBP2, and SCD gene expression when compared to the HFDC group. In addition, the mice treated with 20mg/kg and 30 mg/kg of ABZ methanolic extract showed a significant reduction of TNFα and IL-6 and significant increase of adiponectin and leptincompared to the HFDC. In conclusion, the antioxidant properties of 20mg/kg to 30 mg/kg methanolic extract of ABZ bark is able to avert obesity by regulation of the genes and adipocytokines involved in lipid metabolism.